Growth and Development Characteristics of Elementary School Students: Implications for Developmentally Appropriate Teaching Strategies - Inayatul Ummah; Halwa Hulyatul Husna (Journal of Asian Primary Education (JoAPE), 2026)
This literature review analyzes the characteristics of growth and development among elementary school students aged 6–12 years and examines their implications for teaching strategies in primary education settings. The school-age period represents a critical phase characterized by relatively stable physical growth and the cognitive transition toward the concrete operational stage, as described by Jean Piaget. Drawing upon primary sources from reputable educational journals and classical developmental psychology theories, this study identifies key patterns in physical, cognitive, social, and emotional development. The findings reveal that many learning difficulties observed in elementary classrooms stem not from low intellectual capacity but from a mismatch between instructional methods and students’ developmental readiness. Effective teaching strategies must therefore integrate an understanding of fine motor skill development (particularly during the 8–9-year “golden period”), the need for concrete learning experiences, and attention to nutritional and environmental factors that influence developmental trajectories. The review emphasizes that synergy between teachers and parents is essential for creating a supportive ecosystem that optimizes children’s holistic growth. Recommendations are provided for implementing developmentally appropriate practices that align pedagogical approaches with children’s biological and psychological stages in both public and Islamic elementary schools.